Mitochondrial ROS-induced lysosomal dysfunction impairs autophagic flux and contributes to M1 macrophage polarization in a diabetic condition. (14th August 2019) - Yuan, Yujia; Chen, Younan; Peng, Tianqing; Li, Lan; Zhu, Wuzheng; Liu, Fei; Liu, Shuyun; An, Xingxing; Luo, Ruixi; Cheng, Jingqiu; Liu, Jingping; Lu, Yanrong
Abstract: Macrophage polarization toward the M1 phenotype and its subsequent inflammatory response have been implicated in the progression of diabetic complications. Despite adverse consequences of autophagy impairment on macrophage inflammation, the regulation of macrophage autophagy under hyperglycemic conditions is incompletely understood. Here, we report that the autophagy–lysosome system and mitochondrial function are impaired in streptozotocin (STZ)-induced diabetic mice and high glucose (HG)-stimulated RAW 264.7 cells. Mitochondrial dysfunction promotes reactive oxygen species (ROS) production and blocks autophagic flux by impairing lysosome function in macrophages under hyperglycemic conditions. Conversely, inhibition of mitochondrial ROS by Mito-TEMPO prevents HG-induced M1 macrophage polarization, and its effect is offset by blocking autophagic flux. The role of mitochondrial ROS in lysosome dysfunction and M1 macrophage polarization is also demonstrated in mitochondrial complex I defective RAW 264.7 cells induced by silencing NADH:ubiquinone oxidoreductase subunit-S4 (Ndufs4). These findings prove that mitochondrial ROS plays a key role in promoting macrophage polarization to inflammatory phenotype by impairing autophagy–lysosome system, which might provide clue to a novel treatment for diabetic complications.